PENINGKATAN HASIL BELAJAR TEMA BERBAGAI PEKERJAAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK PADA SISWA KELAS IV - Rizka Fadhila, Desyanti; Adianto, Samsul (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
This study was to improve student learning outcomes when implementing the Talking StickLearning Modelt in Thematic Learning with the theme Types of Job on the subject of Social Sciences Discussion for students class IVB at SDN 010 North Samarinda 2019/2020. In this study, the subjects were students class IVB in the first semester of academic year 2019/2020 with a total of 30 students. The data were collected by interviews, observation and documentation towards the research subjects.Based on the research result, it coulds be concluded that using the talking stick model could improve the learning outcomes of students. The pre-cycle with an average value of learning outcomes in the cognitive aspect was 65.56 with a percentage of 40% completeness then slowly the student's score increases in the first cycle to 68.1 with a percentage of 53.33% completeness. Then in cycle II the average value of student learning outcomes increased again to 84.5 with a percentage of 100%. Likewise with students’ learning outcomes in the psychomotor aspect, in the first cycle the average score was 66.7 with a percentage of 33.33% completeness, then in the second cycle it increased to 80.5 with a percentage of 86.66% completeness. Keywords:Talking Stick Learning Model, Learning Outcomes.